2023
DOI: 10.7150/ijbs.86475
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins as potential communicators play an essential role in the pathogenesis and treatment of early atherosclerosis

Yang Li,
Xinyi Luo,
Zhenglai Hua
et al.

Abstract: Atherosclerosis as the leading cause of the cardiovascular disease is closely related to cholesterol deposition within subendothelial areas of the arteries. Significantly, early atherosclerosis intervention is the critical phase for its reversal. As atherosclerosis progresses, early foam cells formation may evolve into fibrous plaques and atheromatous plaque, ulteriorly rupture of atheromatous plaque increases risks of myocardial infarction and ischemic stroke, resulting in high morbidity and mortality worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 157 publications
0
3
0
Order By: Relevance
“…ApoB emerges as a pivotal player in the proatherogenic cascade. By interacting with proteoglycans in the extracellular matrix, ApoB facilitates the retention and aggregation of surplus cholesterol-rich lipoproteins within the subendothelium of the arterial wall-an essential initial step in AS formation (41,42). Lipoproteins containing ApoB with a diameter less than 70 nm, including CM remnants, VLDL, VLDL remnants, IDL, and LDL, can efficiently traverse the intact endothelium, allowing products from TRLs metabolism, except de novo CM, to accumulate beneath the vascular endothelium (43).…”
Section: Trls Promotes As By Subendothelial Accumulationmentioning
confidence: 99%
“…ApoB emerges as a pivotal player in the proatherogenic cascade. By interacting with proteoglycans in the extracellular matrix, ApoB facilitates the retention and aggregation of surplus cholesterol-rich lipoproteins within the subendothelium of the arterial wall-an essential initial step in AS formation (41,42). Lipoproteins containing ApoB with a diameter less than 70 nm, including CM remnants, VLDL, VLDL remnants, IDL, and LDL, can efficiently traverse the intact endothelium, allowing products from TRLs metabolism, except de novo CM, to accumulate beneath the vascular endothelium (43).…”
Section: Trls Promotes As By Subendothelial Accumulationmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that although apolipoproteins have often been ignored in the biochemical detection of blood lipids, their contribution to the pathogenesis of early atherosclerosis may exceed our imagination. [25][26][27][28] As a communicator of lipoprotein, apolipoprotein can mediate the activation of vascular endothelial cells (ECs), and the activated vascular ECs produce interleukin-6 (IL-6), intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and other cytokines. These factors stimulate the recruitment of monocytes and adhesion to ECs, prompting monocytes to pass through endothelial tissues and transform into macrophages.…”
mentioning
confidence: 99%
“…These factors stimulate the recruitment of monocytes and adhesion to ECs, prompting monocytes to pass through endothelial tissues and transform into macrophages. 25 Apo B in apolipoprotein acts as a ligand-mediated LDL to bind to the LDL receptor (LDLR) to promote cholesterol uptake in peripheral tissues. Meanwhile, apo B causes excessive LDL to accumulate under the vascular endothelial by interacting with proteoglycan in the extracellular matrix, initiating the formation of atherosclerosis.…”
mentioning
confidence: 99%